Dissecting apicoplast functions through continuous cultivation of Toxoplasma gondii devoid of the organelle - Min Chen; Szilamér Gyula Koszti; Alessandro Bonavoglia; Bohumil Maco; Olivier von Rohr; Hong-Juan Peng; Dominique Soldati-Favre; Joachim Kloehn (Nature Communications, 2025)
Abstract The apicoplast, a relic plastid organelle derived from secondary endosymbiosis, is crucial for many medically relevant Apicomplexa. While it no longer performs photosynthesis, the organelle retains several essential metabolic pathways. In this study, we examine the four primary metabolic pathways in the Toxoplasma gondii apicoplast, along with an accessory pathway, and identify conditions that can bypass these. Contrary to the prevailing view that the apicoplast is indispensable for T. gondii, we demonstrate that bypassing all pathways renders the apicoplast non-essential. We further show that T. gondii lacking an apicoplast (T. gondii −Apico) can be maintained indefinitely in culture, establishing a unique model to study the functions of this organelle. Through comprehensive metabolomic, transcriptomic, and proteomic analyses of T. gondii −Apico we uncover significant adaptation mechanisms following loss of the organelle and identify numerous putative apicoplast proteins revealed by their decreased abundance in T. gondii −Apico. Moreover, T. gondii −Apico parasites exhibit reduced sensitivity to apicoplast targeting compounds, providing a valuable tool for discovering new drugs acting on the organelle. The capability to culture T. gondii without its plastid offers new avenues for exploring apicoplast biology and developing novel therapeutic strategies against apicomplexan parasites.